Determination of calf circumference cut-off values for Malaysian elderly and its predictive value in assessing risk of malnutrition - H., Sakinah; A., Siti NurAsyura; S., Suzana (Nutrition Society of Malaysia, 2016)
Introduction: Malnutrition is a growing problem but quite often under-recognised in elderly people. Calf circumference (CC) is a simple measurement that can be used to identify elderly people who are at high risk of malnutrition; however, a population-specific cut-off point must be developed. Therefore, this study aimed to determine suitable cut-off points and evaluate the predictive value of the CC cut-off point for elderly Malaysians. Methods: A total of 820 persons comprising 433 men and 387 women were recruited as subjects. The mean age was 69.0 ± 6.8 and ranged between 60 to 97 years. Data were collected from Sabak Bernam, Selangor Kuala Pilah, Negeri Sembilan; Pasir Mas, Kelantan, and Kodiang, Kedah. A linear regression analysis with the z-score procedure by gender was used to derive the CC prediction equations. Results: The CC cut-off points for men and women at risk of malnutrition were 30.1 cm and 27.3 cm, respectively. The final predictive CC equations for men was CC (cm) = 3.69 (z score) + 33.81, R2 = 1 and CC (cm) = 0.7103 (BMI) + 18.54, R2 = 1; and for women, CC (cm) = 4.31 (z score) + 31.63, R2 = 1 and CC (cm) = 0.6698(BMI) + 16.847, R2 = 1. Based on these equations, using the z-score equal to negative 1 for men (BMI 16.30 kg/m2) and women (BMI 15.64 kg/m2), the mean of the predictive value of the CC cut-off point was 32.0 ± 4.2 cm in men and 30.5 ± 4.6 cm in women. Conclusion: It is suggested that these cut-off points be used to screen elderly individuals who are at risk of malnutrition. Further studies should be undertaken to further verify the application of the findings of this study.